PARTISIPASI MASYARAKAT TERHADAP PROGRAM PENDIDIKAN ANAK USIA DINI DESA BULO WATTANG KABUPATEN SIDENRENG RAPPANG - Suryani Syam; Kamaruddin Sellang; Andi Sinrang; Muhammad Nur (FISIP Universitas Muhammadiyah Sidenreng Rappang, 2022)
The purpose of knowing the Population Participation in the Early Childhood Learning Program (PAUD) in Bulo Village, Panca Rijang District, Sidenreng Rappang Regency, and to find out what factors influence the population's participation in the Early Childhood Learning Program (PAUD) in Bulo Village, Panca Rijang District, District Sidenreng Rappang. The population in this case is 105 people who have children aged 2-6 years. On the other hand, the illustration used is purposive sampling, using quantitative descriptive research, and the collection method is through observation, questionnaires, documentation, and library research. Information analysis method used is descriptive statistics, test the quality of information using a frequency table. The results of the research show that community participation in Bulo Village is in the poor category with a percentage of 59.5% of the factors that influence community participation with an accumulation of 60% in the less influential category.